Developing Interactive Media Based On Flash For Competency Student (cognitive domain) in Bloodstream System - Dicky Halin Wijana Ashidiq; Rizhal Hendi Ristanto; Mieke Miarsyah (Indonesian Journal of Biology Education, 2020)
Misconceptions are often experienced by the students of senior high school. Especially on the learning material of circulatory system. The aim of this study is to develop Biology instructional media in the form of Adobe Flash-based interactive instructional media on the learning material of Circulatory System which the content is designed to improve the students’ competencies. The development of this instructional media uses the RnD method with the Borg and Gall development model. There are 3 validators consisting of 2 Biology material experts and 1 instructional media expert who will test and validate the media that is developed. The study to test the effectiveness of the media is a before-after experimental design. The validation of media done by material and media experts shows the result that is categorized as very good, and the result of statistical test with paired sample t-test shows a significance value of 0.00 < 0.05. This means that there is a significant difference in the average score of students from before and after using Adobe Flash-based interactive instructional media to improve students’ competencies. Thus, the Adobe Flash-Based Interactive instructional media can improve the competencies of students.